Worldview Islam sebagai Basis Pengembangan Ilmu Fisika - Aldy Pradhana; Yongki Sutoyo (Universitas Darussalam Gontor, 2019)
AbstractThe development and progress of science and technology today cannot be separated from physics. Through physics, various benefits have been presented to human life, for example in the fields of industry, transportation of information and communication. However, behind the variety of benefits that have been presented it turns out to contain serious problems, namely the crisis of morality and spirituality. The emergence and development of the problem is rooted in the secular physicist worldview, where God and religion are not central and influential in scientific activity. This is diametrically different from the Worldview of Islam which makes God the basis for the development of science. Thus, Islam does not experience problems regarding the relationship of religion and science. This includes physics which has been proven factually by previous Islamic scientists. That is, worldview so designate how physics is developed. So, in this article will be described the variant of problems related to worldview, which are believed and used by physicists, in developing physics and technology and how the worldview of Islam responds to these problems as an alternative to the development of physics. The worldview of Islam, if held consistently by Muslim scientists as a basis for the development of physics, will have the following implications: First, the shift in physicists' worldview; Second, giving orientation to physicists' scientific works; Third, encourage improvement, refinement, re-formulation of physics theory and how technology is produced and its actualization; Fourth, if the first to third points are actualized to physicists on a broad scale, then the scientific culture nowadays is most likely to shift; Fifth, it is possible to shift the scientific paradigm.Keywords: Worldview, Tawhid, Physics, Secular, Implications. AbstrakPerkembangan dan kemajuan ilmu pengetahuan serta teknologi yang begitu pesat dewasa ini tidak bisa dilepaskan dari ilmu fisika. Lewat ilmu fisika, ragam kebermanfaatan telah dihadirkan bagi kehidupan manusia, misalnya dalam bidang industri, transportasi informasi dan komunikasi. Namun dibalik ragam kebermanfaatan yang telah dihadirkan itu ternyata mengandung problem serius, yakni krisis moralitas dan spiritualitas. Muncul dan berkembangnya problem tersebut berakar dari worldview Fisikawan yang sekuler, dimana Tuhan dan agama menjadi tidak sentral dan berpengaruh dalam aktivitas ilmiah (scientific activity). Hal ini berbeda secara diametris dengan pandangan hidup Islam yang menjadikan Tuhan sebagai basis dalam pengembangan ilmu pengetahuan. Sehingga Islam tidak mengalami persoalan perihal relasi agama dan ilmu pengetahuan. Hal ini termasuk ilmu fisika yang telah dibuktikan secara faktual oleh para ilmuwan Islam terdahulu. Artinya, pandangan hidup begitu menentukan bagaimana ilmu fisika dikembangkan. Maka dalam artikel ini akan dipaparkan varian persoalan terkait worldview yang diyakini dan digunakan oleh para fisikawan dalam mengembangkan ilmu fisika dan teknologi, serta bagaimana the worldview of Islam merespon persoalan itu sebagai sebuah alternatif bagi pengembangan ilmu fisika. The worldview of Islam, jika dipegang secara konsisten oleh ilmuwan Muslim sebagai dasar pengembagan ilmu fisika, maka akan menghadirkan implikasi-implikasi sebagai berikut: Pertama, pergeseran pandangan hidup fisikawan; Kedua, memberikan orientasi pada kerja-kerja saintifik fisikawan; Ketiga, mendorong terjadinya perbaikan, penyempurnaan, perumusan ulang teori ilmu fisika serta bagaimana teknologi diproduksi dan aktualisasinya; Keempat, apabila poin pertama sampai ketiga teraktualisasi pada fisikawan dengan skala yang luas, maka berpotensi menggeser budaya ilmiah yang ada saat ini; Kelima, memungkinkan terjadinya pergeseran paradigma keilmuan.Kata Kunci: Worldview, Tauhid, Ilmu Fisika, Sekuler, Implikasi.